Gelatinolytic activity of autocrine matrix metalloproteinase-9 leads to endothelial de-arrangement in Moyamoya disease. Issue 11 (November 2018) - Blecharz-Lang, Kinga G; Prinz, Vincent; Burek, Małgorzata; Frey, Dietmar; Schenkel, Tobias; Krug, Susanne M; Fromm, Michael; Vajkoczy, Peter
Moyamoya disease (MMD) is a rare steno-occlusive cerebrovascular disorder. Mechanisms driving the formation of aberrant MMD vessels remain elusive. We collected serum and vessel specimens from MMD and atherosclerotic cerebrovascular disease (ACVD) patients serving as controls due to the same hypoxic stimulus but substantial differences in terms of vascular features. Based on patient material and an in vitro model mimicking ACVD and MMD conditions, matrix metalloproteinase-9 (MMP-9) and vascular-endothelial growth factor (VEGF) were tested for their potential involvement in cerebrovascular disintegration. While serum concentration of both molecules did not significantly differ in both patient groups, excessive collagenase activity and lowered collagen IV protein amount in MMD vessels pointed to a focal MMP-9 activity at the affected vessel sites. We observed overexpressed and autocrinely secreted MMP-9 and VEGF along with disturbances of EC–matrix interactions in MMD but not ACVD serum-treated cEND cells. These seemingly brain-specific effects were partially attenuated by VEGF signaling inhibition suggesting its role in the MMD etiology. In conclusion, our findings support the understanding of the high incidence of hemorrhagic and ischemic events in MMD and provide the basis for novel therapeutic strategies stopping or slowing the development of fragile cerebrovasculature or micro-bleeds characterizing the disease.